Feasibility of aspirin and/or vitamin D3 for men with prostate cancer on active surveillance with Prolaris® testing. Issue 6 (11th June 2022) - Dinneen, Eoin; Shaw, Gregory L.; Kealy, Roseann; Alexandris, Panos; Finnegan, Kier; Chu, Kimberley; Haidar, Nadia; Santos‐Vidal, Sara; Kudahetti, Sakunthala; Moore, Caroline M.; Grey, Alistair D. R.; Berney, Daniel M.; et al.
Abstract: Objectives: To test the feasibility of a randomised controlled trial (RCT) of aspirin and/or vitamin D3 in active surveillance (AS) low/favourable intermediate risk prostate cancer (PCa) patients with Prolaris® testing. Patients and Methods: Newly‐diagnosed low/favourable intermediate risk PCa patients (PSA ≤ 15 ng/ml, International Society of Urological Pathology (ISUP) Grade Group ≤2, maximum biopsy core length <10 mm, clinical stage ≤cT2c) were recruited into a multi‐centre randomised, double‐blind, placebo‐controlled study (ISRCTN91422391, NCT03103152). Participants were randomised to oral low dose (100 mg), standard dose (300 mg) aspirin or placebo and/or vitamin D3 (4000 IU) versus placebo in a 3 × 2 factorial RCT design with biopsy tissue Prolaris® testing. The primary endpoint was trial acceptance/entry rates. Secondary endpoints included feasibility of Prolaris® testing, 12‐month disease re‐assessment (imaging/biochemical/histological), and 12‐month treatment adherence/safety. Disease progression was defined as any of the following (i) 50% increase in baseline PSA, (ii) new Prostate Imaging‐Reporting and Data System (PI‐RADS) 4/5 lesion(s) on multi‐parametric MRI where no previous lesion, (iii) 33% volume increase in lesion size, or radiological upstaging to ≥T3, (iv) ISUP Grade Group upgrade or (v) 50% increase in maximum cancer core length. Results: Of 130 eligible patients, 104 (80%) accepted recruitment from seven sites over 12 months, of which 94 patients represented the per protocol population receiving treatment. Prolaris® testing was performed on 76/94 (81%) diagnostic biopsies. Twelve‐month disease progression rate was 43.3%. Assessable 12‐month treatment adherence in non‐progressing patients to aspirin and vitamin D across all treatment arms was 91%. Two drug‐attributable serious adverse events in 1 patient allocated to aspirin were identified. The study was not designed to determine differences between treatment arms. Conclusion: Recruitment of AS PCa patients into a multi‐centre multi‐arm placebo‐controlled RCT of minimally‐toxic adjunctive oral drug treatments with molecular biomarker profiling is acceptable and safe. A larger phase III study is needed to determine optimal agents, intervention efficacy, and outcome‐associated biomarkers.